The Effect of Family Support, Leader Support, and Work-Life Balance on Teacher Performance in Pringsewu Regency - Debby Anggriansyah; Ika Nurul Qamari; Nuryakin Nuryakin (Universitas Mercu Buana, 2022)
Objectives: The purpose of this study was to determine the effect of family support, leader support, and work-life balance on teacher performance.Methodology: The sampling technique used is non-probability sampling and uses a purposive sampling technique. This study used a sample of 150 teachers in Sukoharjo District, Pringsewu Regency, Lampung. The analysis of this research used SEM with AMOS 24.0 software.Finding: The results showed that family support has a significant effect on teacher performance. Family support has a significant effect on the work-life balance of teachers. Leader support has a significant effect on the work life balance of teachers. Leader support has a significant effect on teacher performance. Work life balance has no significant effect on teacher performance.Conclusion: The conclusion of this study is that family support and leader support have a significant effect on teacher performance, family support and leader support have a significant effect on work-life balance, and work-life balance has no significant effect on teacher performance. In the process of achieving a balance between the